PENGEMBANGAN LKPD BERBASIS PENDIDIKAN MULTIKULTURAL PADA PEMBELAJARAN PPKN KELAS IV SD - Iffa Karimah; Nina Nurhasanah; Dudung Amir Soleh (Universitas Trilogi, 2021)
The aim of this research and development is to develop the student worksheet based on multicultural education for PPKn lesson in IV grade elementary school. The research method used is research and development with the ADDIE development model. There are 5 steps in the ADDIE model, namely analysis, design, development, implementation and evaluation. The technique of collecting data used in this research are interview and questionnaires. The data analysis technique used in this research and development is descriptive statistics. Student worksheets are validated by involving 3 experts, including material experts, media experts, and language experts. The subjects of the study were 4th grade students, totaling 4 students for the one to one evaluation and 12 students for the small group evaluation. The results showed that the student worksheets based on multicultural education for PPKn lesson in IV grade elementary school were included in the very good category with a percentage of 90.90% by material experts, 92.85% by linguists and 93.75% by media experts. Trials on students were included in the very good category at the step one to one evaluation of 95.95% and the small group evaluation of 97.91%. This shows that worksheet is feasible to be used as a learning resource in PPKn lesson.